2021
DOI: 10.3389/fphys.2021.642703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Small-Sided Games vs. Running-Based High-Intensity Interval Training on Physical Performance in Soccer Players: A Meta-Analytical Comparison

Abstract: Objectives: This systematic review with meta-analysis (SRMA) was conducted to compare the effects of SSG-based interventions vs. running-based HIIT interventions on soccer players' sprinting time (ST), vertical height jump (VJH), and change of direction time (CODt).Data Sources: The data sources utilized were Web of Science, Scopus, SPORTDiscus, and PubMed.Results: An electronic search yielded 650 articles, six of which were included in the present study. Between-group analysis found a significant favoring eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 54 publications
9
39
3
Order By: Relevance
“…This fact was not observed in a previous study that combined SSGs and endurance and speed training or in the study that combined SSGs and short-interval (15 -15 ) HIIT [15]. In fact, recent systematic reviews with meta-analysis revealed inconsistences and the ineffectiveness of SSGs [12] and HIIT [34] in improving linear sprinting in soccer players. One possible reason for observing improvements in the current research is due to the age effect and the capacity for improvement in this sensitive period [36].…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This fact was not observed in a previous study that combined SSGs and endurance and speed training or in the study that combined SSGs and short-interval (15 -15 ) HIIT [15]. In fact, recent systematic reviews with meta-analysis revealed inconsistences and the ineffectiveness of SSGs [12] and HIIT [34] in improving linear sprinting in soccer players. One possible reason for observing improvements in the current research is due to the age effect and the capacity for improvement in this sensitive period [36].…”
Section: Discussionmentioning
confidence: 62%
“…A combination of SSGs and running-based HIIT was recently tested, aiming to provide the advantageous effect of running-based HIIT to the training programmes based on SSGs [12]. The first reported combination of SSGs and HIIT revealed the beneficial effect of the combination compared to a group using just SSGs for the improvement of VO 2max and 30-15 VIFT [15].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations